Alopecia areata—New updates with long‐term use of JAK inhibitors. Issue 3 (12th March 2021) - Nguyen, Cristina; Atanaskova Mesinkovska, Natasha
Abstract: Alopecia areata (AA) is an autoimmune condition of multifactorial etiology that affects about 2% of the general population. It is a disease leading to significant emotional and psychosocial distress. There are very limited treatment options available for AA with no therapy demonstrating sustained remission long term. Understanding the genetic and molecular mechanisms of AA have led to the development of novel molecularly targeted treatments such as the Janus Kinase (JAK) inhibitors. Evidence suggests that JAK inhibitors may be broadly useful in dermatology with promising developments in open‐label clinical trials for AA. Here, the results of long‐term use of JAK inhibitors are reviewed and discussed for moderate‐to‐severe AA.